Two new species of Arisemus Satchell, and first records of A. atrasetus (Rapp) and A. salazari Quate from Mexico (Diptera, Psychodidae) - Durán-Luz, Juana; Ibáñez-Bernal, Sergio (Zootaxa, 2025)
Two new species of Arisemus Satchell from Mexico are described based on male and female specimens collected in a tropical deciduous forest from Puebla, central Mexico. Also, Arisemus atrasetus (Rapp) and A. salazari Quate, are by first time recorded in Mexico. The two new species and A. salazari belong to the group of species characterized by a simple gonostylus, while A. atrasetus belongs to the group with bifid or trifid gonostylus.